2008
DOI: 10.2353/ajpath.2008.070559
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cells Regulate the Magnitude and the Cytokine Microenvironment of the Contact Hypersensitivity Response

Abstract: The role that mast cells play during contact hypersensitivity (CS) response is unclear because some studies have shown that mast cell-deficient mice have relatively intact CS responses whereas others have shown opposing results. Mast cells secrete a wide range of immunomodulatory mediators and can potentially influence the type of immune response generated in the skin during CS. Therefore, we examined the type of microenvironment generated during CS in both W/Wv mast cell-deficient and wild-type mice in respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
36
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 40 publications
5
36
0
Order By: Relevance
“…Although some accumulation of mast cells was observed on challenge of the footpad, cell recruitment was irrespective of antigen presence or selectin-ligand expression (unpublished data). A recent study by Norman and colleagues 40 showed that the presence of mast cells affects the differentiation of T cells in a contact hypersensitivity reaction. Considering the missing effect of mast cells in our model that relies on the in vitro differentiation of Th1 cells the Ϫ/Ϫ ϫ DO11.10 mice were transferred into WT and FucT-VII Ϫ/Ϫ mice, respectively.…”
Section: Cellular Players In a Dthmentioning
confidence: 99%
“…Although some accumulation of mast cells was observed on challenge of the footpad, cell recruitment was irrespective of antigen presence or selectin-ligand expression (unpublished data). A recent study by Norman and colleagues 40 showed that the presence of mast cells affects the differentiation of T cells in a contact hypersensitivity reaction. Considering the missing effect of mast cells in our model that relies on the in vitro differentiation of Th1 cells the Ϫ/Ϫ ϫ DO11.10 mice were transferred into WT and FucT-VII Ϫ/Ϫ mice, respectively.…”
Section: Cellular Players In a Dthmentioning
confidence: 99%
“…28,29 As TNCB-induced CHSRs thus share most of the mechanisms characterized for conventional DTHRs, we studied the role of TNFR1 in response to TNCB, using the TNCB-induced CHSR as a model for the DTHR that provides the unique possibility to individually investigate antigen presentation, priming, and differentiation of CD4 and CD8 T cells, cell migration, T cell-mast cell interactions, and mast cell-endothelia interactions with the help of mast cell knock-in experiments. 20,27,[30][31][32] Importantly, it allows the study of these effects largely independently of phenomena, such as antigen processing by APCs. Here, we show that TNFR1 signaling is neither needed for in vivo priming nor for the induction of Th1 cells capable of inducing severe DTHRs.…”
mentioning
confidence: 99%
“…In contrast to DTHR induced by TNCB, IL-4 seems to play a role in the generation of DTHR induced by Oxazolon. 24,26,27 A third frequently used hapten is dinitroflourobenzene (DNFB). DNFB exerts the strongest toxic reactions.…”
mentioning
confidence: 99%
“…Indeed, at least in the Kit W/W-v model, it has been shown that the doses of adjuvant or peptide in immunization protocols can drastically affect MC involvement in the disease under investigation, as emerged in experimental models of asthma 23 and contact hypersensitivity. 24 The aim of our study was to unravel the contribution of MCs to EAE in both Kit W-sh/W-sh and Kit W/W-v strains by using different protocols of immunization, in order to evaluate if disease outcome was affected by different experimental settings. In this study, we report that, under three different immunization conditions, Kit W-sh/W-sh mice develop a more severe EAE and an increased immune response against myelin than Kit þ / þ animals.…”
mentioning
confidence: 99%